Hydroclimatic variability and impacts on water resources of large hydrological catchments in sudanese-sahelian area - (:unkn) unknown (My University, 2004)
Modelling the impact of the expected climate variability on water resources is fundamental for the planning of facilities, mainly in Western Africa subjected to an unprecedented drought since around thirty years. The purpose of that work is to be able to use rainfall and potential evapotranspiration data from climatic scenarios as input to hydrological models; these models being previously calibrated on large catchments from western Africa (Senegal, Gambia, Sassandra) and central Africa (Logone-Chari). Thus, the main goal is to study the likely variability of water resources during the 21st century. That approach is based on: - The knowledge of the variability of rainfall and hydrological regimes. From a general point of view, the 1970 – 1998 period is in deficit regarding rainfall and the 1990 decade demonstrates that the drought is going on. Those deficits can be explained by a modification of the area influenced by the monsoon which takes part in a more global dynamic regarding the atmospheric circulation. - The assessment of tools to model hydrological regimes of large rivers. Two hydrological models, based on balance equations (GR2M and WBM) have been selected. They work at a monthly time step and with data grids established at a resolution of a square half degree. The sensitivity analysis of the models underlines the significance of rainfalls, land cover and land use regarding hydrological modelling. That assessment also emphasizes the quality of the results and the adaptability of the GR2M model. - The elaboration and the use of climatic scenarios from data provided by GCM. Outputs from climatic models are not really reliable but the foreseen variations can be combined with observed data to generate climatic scenarios. From rainfall and temperature data provided by the HadCM3-A2 model, two likely climatic scenarios could be elaborated. Used with GR2M and WBM they lead to the reduction of the Senegal and Gambia flow, to an increase followed by
Keywords: African Research